Spin fluctuation induced linear magnetoresistance in ultrathin superconducting FeSe films. (14th August 2017) - Wang, Qingyan; Zhang, Wenhao; Chen, Weiwei; Xing, Ying; Sun, Yi; Wang, Ziqiao; Mei, Jia-Wei; Wang, Zhengfei; Wang, Lili; Ma, Xu-Cun; Liu, Feng; Xue, Qi-Kun; et al.
Abstract: The discovery of high-temperature superconductivity in FeSe/STO has trigged great research interest to reveal a range of exotic physical phenomena in this novel material. Here we present a temperature dependent magnetotransport measurement for ultrathin FeSe/STO films with different thickness and protection layers. Remarkably, a surprising linear magnetoresistance (LMR) is observed around the superconducting transition temperatures but absent otherwise. The experimental LMR can be reproduced by magnetotransport calculations based on a model of magnetic field dependent disorder induced by spin fluctuation. Thus, the observed LMR in coexistence with superconductivity provides the first magnetotransport signature for spin fluctuation around the superconducting transition region in ultrathin FeSe/STO films.